PENGARUH LINGKUNGAN KERJA DAN INSENTIF TERHADAP KEPUASAN KERJA (STUDI PADA PETUGAS LABORATORIUM PUSKESMAS DI KABUPATEN LOMBOK BARAT ) - lalu samsu rizali (Master of Management, Mataram University, 2017)
This research is aimed at determining the effect of work environment and incentives on the work satisfaction of health center laboratory workers in West Lombok. The population of this research are all 40 workers of health center laboratory in West Lombok. The analysis is completed with multiple linear regression. The research showed that work environment and incentive simultaneously have positive and significant effect on the work satisfaction. Partially, work environment has positive a significant effect on work satisfaction and incentive has positive and significant effect on work satisfaction. Work environment has more dominant effect comparing to the incentive effect on the work satisfaction of workers of health center laboratory in West Lombok.Keywords : Work Satisfaction, Work Environment, Incentive.